Analysis of the Spread of Gripep and the Control of Its Symptoms in Indonesian Society - Kusumawati, Prima Dewi; Kurniati, Ana; Putri, Elvina Triana; Amri, Choirul; Koesnadi, Koesnadi (PT Inovasi Pratama Internasional, 2025)
This study investigates the emergence and impact of